2008
DOI: 10.1109/toh.2008.20
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Transparency in Tactile Information Design

Abstract: Abstract-This paper places contemporary literature on the topic of unimodal single-site display of information using complex tactile signals in the context of progress toward transparent communication-placing minimal load on the user's attentional resources. We discuss recent evidence that more is possible with purely haptic display than is commonly believed, as well as procedural developments that support systematic design of transparent tactile information display, and we frame the advances required to reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Hence, the simplest tactons were the ones chosen as a starting point to facilitate the everyday use of the HMI. Additionally, due to the abstract meaning-stimulus relationship, this set of tactons scales better than those that use a more mnemonic meaning-stimulus relationship [33]. Also, this method is faster and easier to decode than those that only transmit characters.…”
Section: Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the simplest tactons were the ones chosen as a starting point to facilitate the everyday use of the HMI. Additionally, due to the abstract meaning-stimulus relationship, this set of tactons scales better than those that use a more mnemonic meaning-stimulus relationship [33]. Also, this method is faster and easier to decode than those that only transmit characters.…”
Section: Apparatusmentioning
confidence: 99%
“…We found that often deaf-blind people are not receptive to learn this new code. Additionally, it has been shown that this kind of abstract representation with messages scales better [33] and makes communication faster and more customizable.…”
Section: Instruction Procedures For the Dbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research on haptic icon design, summarized in [27], provides a start for finding salient yet unintrusive tactile mappings for cues. Icons for progress updates, errors, and warnings provide insights for presentation cues [15,44].…”
Section: Tactile Perception: Body Locale and Iconographymentioning
confidence: 99%
“…Transparency refers to the capability of the controller to compensate (feedforward controller) for hardware imperfections such as inertia, friction, backlash and vibration such that the payload and mechanism are hidden while a model (impedance or admittance) is rendered to the user. 18 Two frequency bandwidths are considered here, in accordance with human perception of vibration (properties of skin mechanoreceptors) 19,17,20 and with human musculoskeletal response (properties of the human body model). 21 It has been found previously that a typical operator is able to control a frequency lower than 10 Hz (i.e.…”
Section: Introductionmentioning
confidence: 99%